Enhancing the resilience of food production systems for food and nutritional security under climate change in Nepal - Neupane, Nilhari; Paudel, Shishir; Sapkota, Regan; Joshi, Yadav Prasad; Rijal, Yashoda; Chalise, Anisha (Frontiers in Sustainable Food Systems, 2022)
Background: Climate change in Nepal has posed a considerable challenge to agricultural productivity and threatened food and nutritional security at multiple levels. This study aims to assess the impacts of changing climate on national food production, and food and nutritional security along with documenting the issue-based prioritized adaptation options for a resilient food production system. Methods: This study considers temperature, precipitation and its anomalies as key factors affecting food production in Nepal. Precipitation trends at the national levels were assessed along with their association with annual production of major cereal crops in Nepal using data from 1990 to 2018. Annual productions of major cereal crops were summed and normalized to calculate production index scores in districts. The scores were plotted and visualized into maps using Geographical Information System. Distribution of flood and extreme rainfall events and malnutrition cases from 2005 to 2018 in three ecological regions were plotted. Climate change impacts and prioritized adaptation options in district level were documented from review of national policies, literatures, and qualitative research based on Focus Group Discussions. Results: In between 1990-2018, overall average production of major cereal crops in Nepal increased by around 2,245 metric tons annually. In district-level index analysis, highest production score was found for Jhapa and Morang while lowest production score was at Humla. Malnutrition in some districts coincided with flood and heavy rainfall events referring that climate change and climate extremes have a role to play in food production and security. Growing drought tolerant crops, change in cropping cycle, riverbed farming practices, developing short-term strategies such as contingency crop planning, changing planting dates, planting short duration varieties, and long-term strategies such as encouraging resettlement programs with transformative livelihood options and sustainable agricultural practices were found key prioritized adaptation measures for a resilient food production systems. Conclusion: In Nepal, changing climate and increasing climate extreme events are adversely affecting food production system which has become a serious threat for food and nutritional security. Implementation of evidence-based practices to build a resilient food system specific to climate vulnerable hotspots in district and local levels is current need of the nation.